EDUCATIONAL ENVIRONMENT IN THE TRANSITION PHASE OF CURRICULUM AT AYUB MEDICAL COLLEGE ABBOTTABAD, PAKISTAN - Khan, Muhammad Junaid; Jamil, Brekhna; Sethi, Ahsan; Noor, Uswah; Javed, Hamza; Humera Adeeb (Journal of Ayub Medical College Abbottabad, 2021)
Background: Evaluation of the educational environment is key to the delivery of high-quality medical education. Especially, when an institute is in the transition phase of curriculum. In curriculum transformation phase of Ayub Medical College Abbottabad, no such evaluation has been done. This study aimed to find the direction of Educational environment in the transition phase curriculum of Ayub Medical College Abbottabad and compare different domains of educational environment with gender, residency, pre-medical education’s medium of instruction, and doctors among sibling or parents. Methods: This descriptive cross-sectional survey was conducted among students of integrated and traditional curriculum of Ayub Medical College, Abbottabad from 1st December 2019 to 29th February 2020. By Non-probability convenience sampling technique, pre-validated Dundee Ready Educational Environment Measure questionnaire was used. Descriptive and inferential statistics were calculated in SPSS v22 Results: A total 149 (100%) participants, 66 (44.3%) males and 83 (55.7%) females with mean age of 20.5±1.07 years responded. Among total, 76 (51%) were from integrated curriculum and 73 (49%) were of traditional curriculum. Significant difference was found among different aspect of educational environments and both classes. Conclusion: The current transitional phase of curriculum at Ayub Medical College Abbottabad is more positive than negative. Some areas like student social-self-perception still need improvement. Moreover, gender and place of birth affect student’s perception about their learning environment.